Multiple antibiotic-resistant Salmonella enterica serovars Enteritidis and Typhimurium in ready-to-eat battered street foods, and their survival under simulated gastric fluid and microwave heating - Sandrasaigaran, P.; Kuan, C. H.; Radu, S.; U. Z. Abidin, U. F.; Rukayadi, Y.; New, C. Y.; Hasan, H. (Elsevier, 2022)
Cooked battered products like nuggets and sausages are famous street foods in Malaysia. However, these foods lack prevalence data for the non-typhoidal Salmonella enterica serovars Enteritidis and Typhimurium (NTS) contaminations, thus leading to concern over foodborne outbreaks. Therefore, the present work aimed to examine the prevalence of antibiotic-resistant NTS in battered foods, and investigate their survival under simulated gastric fluid (SGF) and microwave heating. Food samples (n = 312) were homogenized, prepared in triplicate tubes (10−1, 10−2, 10−3), and subjected to a combined most probable number (MPN) statistical analysis and multiplex-touchdown PCR amplification for NTS detection. The tubes with bacterial growth were cultured on Xylose Lysine Deoxycholate (XLD) agar, and isolated NTS were subjected to antibiotic susceptibility (disk diffusion) and survival tests in SGF (pH: 2.0, 3.0, 4.0, and 7.0) and microwave heating. Results showed that S. Enteritidis and Typhimurium contaminated 5.1% and 1.6% of battered foods, respectively. Pork sausage yielded the highest S. Enteritidis concentration (150 MPN/g), and beef sausage yielded the highest S. Typhimurium (28 MPN/g) concentration. Four S. Enteritidis and one S. Typhimurium strains exhibited multiple antibiotic resistance to cefazolin, ampicillin, streptomycin, tetracycline, sulfonamides, nalidixic acid, kanamycin, gentamycin, and chloramphenicol. The NTS strains were also resistant to SGF at all tested pH, but inactivated at microwave heating (700W, 2.45Hz, 60 s). These indicated that NTS contamination in cooked battered foods was low. However, multiple antibiotics and SGF resistance might imply severe consequences if proper interventions were not taken.